A metric for measuring power efficiency and data throughput in mobile ad hoc networks. Issue 5 (3rd September 2019) - Newton, Todd A.; John, Eugene B.
ABSTRACT: Mobile ad hoc networks (MANET) are becoming increasingly popular, particularly in the realm of sensor networks. However, most of the ongoing research is centered on protocol development or data delivery characteristics, particularly in the areas of throughput and latency. But in the realm of wireless networks, a new metric needs to be considered, one that takes into consideration the power efficiency across the wireless network. Wireless nodes have a finite amount of energy to operate with, and when that energy is depleted, the node dies and no longer performs its intended functions. In order to maintain a functioning MANET for longer periods of time, the network as a whole needs to be optimized for power efficiency. Ongoing research in the realm of MANETs includes the development of power-aware routing algorithms. A number of them have been developed, often augmenting existing routing protocols. To aid in the validation of network performance improvement, this paper describes a metric that incorporates both power efficiency and data throughput of MANETs. This new network performance metric can be used for selecting the optimal routing protocol for the network scenario. GRAPHICAL ABSTRACT: